Atropine‐induced toxicity after off‐label sublingual administration of eyedrop for sialorrhoea treatment in neurological disabled patients. Issue 8 (23rd February 2021) - Michelon, Hugues; Larabi, Islam Amine; Lemoine, Jérôme; Alvarez, Jean‐Claude; Genevée, Anne; Lillo‐Lelouet, Agnès; Azouvi, Philippe; Lefèvre‐Dognin, Clémence; Paquereau, Julie
Abstract : Sialorrhea is a troublesome and disabling symptom defined by the unintentional loss of saliva from the mouth, usually associated with swallowing disorders. Today there is no consensus about the management of sialorrhoea, but off‐label use of ophthalmic atropine eyedrop administered sublingually may offer benefits, despite limited safety data. We report 2 cases of atropine overdose after sublingual administration illustrating that atropine can expose to severe adverse effects when administered sublingually. The noncompartmental pharmacokinetic study of atropine performed in 1 patient highlighted that systemic absorption of sublingual atropine was effective (Cmax [1 h] = 2.2 ng mL −1 ; approximately) after a single dose of 1 mg.